Efficacy and safety of belimumab in lupus nephritis patients: a real-world observational study in China - Meng Tan; Jing Xu; Ying Tan; Zhen Qu; Feng Yu; Minghui Zhao (Karger Publishers, 2023)
BACKGROUND: This study aimed to describe disease activity, clinical outcome and overall patterns of lupus nephritis care in patients who received belimumab in a real-world clinical setting in China. MATERIALS AND METHODS: This observational cohort study included lupus nephritis patients who received belimumab as adjunct therapy. We deeply investigated the characteristics of those patients including clinical response to belimumab and safety. RESULTS: All 61 lupus nephritis patients were included with a median follow-up period of 9 months (6,19). Prevalence of proteinuria (52.5% to 24.6%) and hematuria (33.3% to 9.8%) were decreased with a stable level of eGFR at last visit. The percentage of patients achieved complete or partial renal response increased from 47.5% to 78.7% and the proportion of complete or partial renal response in patients with proliferative lupus nephritis was higher than those with membranous lupus nephritis (75% vs. 50%) at last visit. The median SLEDAI score decreased from 6 to 2, and there was an increase in patient of LLDAS from 17 to 33 at last visit. A notable dose reduction was seen for glucocorticosteroid dose, with a median change from 10 to 5 mg/d. The proportion of patients receiving >7.5 mg/d steroids reduced from 52.5% at baseline to 23.0% at last visit. The discontinuation of belimumab was rare (3/61) for drug induced fever, hyperthyroidism and uveitis. CONCLUSIONS: Lupus nephritis patients with belimumab demonstrated improvements in clinical response and a reduction in glucocorticosteroids, which providing evidence of effectiveness and safety in real-world clinical practice in China.